Evaluasi Produksi dan Kualitas Nutrisi pada Bagian Daun dan Kulit Kayu Calliandra callotirsus dan Gliricidia sepium - Daning, Dewi Ratih Ayu; Foekh, Benyamin (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2018)
The aim of our study was to determine the nutrient content and organic matter degradability of different morphological parts (leaves and bark wood) of Calliandra and Gliricidia. Variable observations were fresh production of leaves and bark wood, diameter and length of plant, proximate analysis, degradability of dry and organic matter. Data was analyzed by independent sample t-test. The results showed that data prodoction of leaves, stems, bark wood on the plant Kaliandra and Gamal was not significant differences (P> 0.05), but the diameter and length of rod between Gamal significantly different (P> 0.05) compared to Kaliandra, furthermore to know nutritional quality and degradability is tested at the Laboratory of Biochemistry Nutrition, Faculty of Animal Science, UGM. The analysis showed that the nutritional quality of the leaves and bark wood of plants Calliandra and Gamal was also no difference, but the value of dry matter and organic matter part of the bark was higher than the leaves.Furthermore, from crop production can be concluded that the both of plant are not significantly different for the data production, but a diameter of gamal steam greater than kaliandra.